Ocular Manifestations in Paediatric Erythema Multiforme: A Case Report: Doi: 10.36351/pjo.v40i4.1863 - Kamal, Ronik Harsono; Dwinastiti, Yasmine Ayu; Winarto , Dewi Alya; Juffry , Sarah Kamiela; Barliana , Julie Dewi (Pakistan Journal of Ophthalmology, 2024)
Erythema multiforme (EM) is a type IV cytotoxic hypersensitivity reaction characterized by classic target lesions on the skin and mucosa, typically affecting the oral, genital, and rarely, ocular mucosa. We describe a 9-year-old girl with widespread rashes, blisters and target lesions on her trunkfor three days. She had eye redness, discomfort, a week-long fever, and a dry cough, without any medication. Ophthalmological examination revealed localized conjunctival injection in her right eye, with no visual impairment or corneal lesions. The diagnosis of EM major (EMM) was based on prior infection, characteristic skin lesions, and mucosal involvement, including ocular manifestation of conjunctival injection. Treatment requires addressing the underlying cause and ophthalmologic consultation for systemic or topical corticosteroids, antibiotics, lubricants, and antihistamines. This case highlights the diagnostic challenges of atypical EM presentations, emphasizing the need for comprehensive evaluation, early recognition, and interdisciplinary collaboration to prevent severe ocular complications and preserve vision.